Seminar Kepedulian Generasi Z terhadap Mental Health sebagai Kunci Sukses Menghadapi Dunia Kerja Era Revolusi 4.0 - Ririn Uke Saraswati; Wisnu Wardana Kusuma; Riyan Syah Yubi; Galih Fabian Kurniadi; Dastia Alfianti; Nida Nadia; Rani Novitasari (BADAN PENERBIT STIEPARI PRESS, 2025)
The seminar “Generation Z's Concern for Mental Health as the Key to Success in Facing the World of Work in the Era of Revolution 4.0” was held at STIE Ekadharma Indonesia with the aim of increasing awareness and understanding of generation Z regarding the importance of mental health in the world of work. This activity was attended by 36 participants from the SMA / SMK level and the general public. Through the presentation of material by resource persons, participants were given insights on how to maintain mental health and strategies to deal with pressure in the world of work. The seminar evaluation results showed a significant increase in participants' understanding of mental health. Indicators of pre-test and post-test results recorded an average increase in the level of understanding of participants by 82.25%. This increase reflects the effectiveness of the seminar in delivering information and equipping participants with the necessary knowledge to face challenges in the Revolution 4.0 era.